Yolqui, a Warrior Summoned from the Spirit World : Testimonios on Violence - Rodríguez, Roberto Cintli, 1954- (Book collections on Project MUSE., 2019)
"Using his own experience of being brutally beaten by police officers in East L.A. as a frame, in this memoir the author reflects on the long history of violence against people of color in the United States. Rodriguez weaves his personal story with historical and current events about violence and the Latino/Indigenous struggle to resist state oppression"--